Effects of Consumption Value on Purchase Intention in Nepalese Hospitality Industry - Basnet, Dinesh; Chhetri, Sampada Ray; Shrestha, Riya; Pati, Pragya (SADGAMAYA, 2025)
The present study investigates the purchase intention of online users within the Nepalese hospitality industry, consisting of consumers who invest considerable amounts for quality accommodation. The objective of this research is to examine the effect of monetary value, quality of benefits value, social status value, information value, and preference value on purchase intention. The methodology is underpinned by a positivist epistemology, while the research design was descriptive and causal in nature and guides the analysis. Primary data has been collected through non-probability (judgmental) sampling from online hospitality consumers, and a quantitative approach has been used. The findings conclude a positive relationship between monetary, information and social status value on purchase intention, while indicating a negative relationship between quality of benefits and preference value with the dependent variable. The study has pinpointed some pivotal factors that affect purchase intention in the hospitality industry in Nepal and guides marketing strategies toward service quality improvement to increase customer satisfaction and loyalty. The hotels of Nepal, though investing much in brand image through costly advertisements, do not recognize consumer behavioral practices.